Code Switching and Code Mixing Phenomena in Construction Area of Paltrow City - KUSUMANINGRUM, FADHILA (LANTERN (Journal on English Language, Culture and Literature), 2016)
Construction area is a place where many kinds of people meet and work as their profession. As a multilingual country, Indonesia not only has many tribesbut also languages. Mostly, Indonesian people use their first language in daily communication. However, in certain moment, they switch or mix their utterances. This study is conducted in contruction area of Paltrow City in Tembalang. The author uses Sadap method in which recorded the speech uttered by the peopleusing a note taking technique. Then, it also uses Padan method to analyze the collected data.In this research, the author finds the phenomena of code switching and code mixing that happen in construction area. Factors that influnce code switching are participant, situation, topic, and the function. Code mixing in this research often happens when they have difficulty in finding appropriate word in Indonesian.